Novel Drug Sensing: Properties and Applications of Amiloride Hydrochloride Membrane - A. Abrahem, Sarra; A. Ibrahim, Suhad (University of Thi-Qar Journal of Science, 2025)
The influence of possible interfering species, such as common inorganic cations, was studied. The construction and electrochemical response characteristics for Amiloride Hydrochloride are described by two electrodes that were prepared based on (Amiloride Hydrochloride, Bromophenol blue as ion pair complex in a PVC matrix and plasticized by two plasticizers, Tri-butyl phosphate (Tri-BP) and Acetophenone (APh). (D1 and D2) are Amiloride Hydrochloride electrodes gave slopes (52.697 and 50.893mV/decade) and the linear range from (10-4-10-2M) for D1and (3*10-4-10-2M) for D2 electrodes. Based on Tri-BP plasticizer, the best electrode (D1) had a slope of 52.697 mV/decade, a detection limit (5×10-6M), a correlation coefficient (0.9997), and a 13-day lifespan. The suggested electrode was used to measure the amount of amiloride hydrochloride in pharmaceutical samples and showed high stability and repeatability. The electrodes were used for the determination of the drug in tablets by potentiometric analysis.